2000
DOI: 10.4315/0362-028x-63.7.976
|View full text |Cite
|
Sign up to set email alerts
|

Kombucha, the Fermented Tea: Microbiology, Composition, and Claimed Health Effects

Abstract: Kombucha is a slightly sweet, slightly acidic tea beverage consumed worldwide, but historically in China, Russia, and Germany. Kombucha is prepared by fermenting sweetened black tea preparations with a symbiotic culture of yeasts and bacteria. Potential health effects have created an increased interest in Kombucha. Yet, only a few research studies have shown that Kombucha has in vitro antimicrobial activity and enhances sleep and pain thresholds in rats. Furthermore, Kombucha consumption has proven to be harmf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
191
0
10

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(203 citation statements)
references
References 14 publications
2
191
0
10
Order By: Relevance
“…The main acetic acid bacteria species found in kombucha were identified as Acetobacter xylinoides, A. pasteurianus, A.xylinum, A. aceti (Chen & Liu, 2000;Greenwalt et al, 2000;Malbasa et al, 2008;Chu & Chen, 2006;Malbasa et al, 2011). Previous studies from our laboratory have shown that kombucha prepared by mixed-culture fermentation with pure strains had a distinctive flavor and short fermentation period (Ma et al, 2008;Xie, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main acetic acid bacteria species found in kombucha were identified as Acetobacter xylinoides, A. pasteurianus, A.xylinum, A. aceti (Chen & Liu, 2000;Greenwalt et al, 2000;Malbasa et al, 2008;Chu & Chen, 2006;Malbasa et al, 2011). Previous studies from our laboratory have shown that kombucha prepared by mixed-culture fermentation with pure strains had a distinctive flavor and short fermentation period (Ma et al, 2008;Xie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This beverage is composed of some probiotics such as acetic acid bacteria and lactic acid bacteria in addition to tea polyphenols, sugars, organic acids, ethanol, water soluble vitamins, and a variety of micronutrients produced during fermentation (Chen & Liu, 2000;Greenwalt et al, 2000;Malbasa et al, 2008). The main acetic acid bacteria species found in kombucha were identified as Acetobacter xylinoides, A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gluconic acid, ethyl-gluconate, oxalic acid, saccharic acid, keto-gluconic, succinic and carbonic acids were considered to be present in kombucha. Some of those acids were proved to have in vitro antimicrobial activity and improve sleep (Greenwalt, Steinkraus, & Ledford, 2000;Sreeramulu, Zhu, & Knol, 2000). Kombucha is a high source of glucuronic acid, which has a detoxifying effect against drug, bilirubin, and chemicals, as well as pollutants and excess of steroid hormones (Nguyen, Nguyen, Nguyen, & Le, 2015).…”
Section: Acetic Acidmentioning
confidence: 99%
“…It is fermented by a symbiotic mixture of bacteria 227 (typically acetic acid bacteria, with small quantities of LAB) and yeast, which are embedded 228 within a cellulosic matrix that floats above the fermentate, similar to the mother cultures of 229 vinegar. Due to the high acid content (as low as pH2), the functionality of kombucha is 230 predominantly due to its physiochemical properties (Greenwalt, Steinkraus, & Ledford, 2000).…”
mentioning
confidence: 99%